Foreign diseases among young people (Journal of Science-Innovative Research in Uzbekistan, 2023)
The author turns to the study of individual preventive measures implemented abroad in order to combat negative factors that threaten the criminological security of the education sector. We are talking about the prevention of suicides of schoolchildren and students, extremism among students, drug addiction, substance abuse and alcoholism among participants in educational relations